Strategizing Learning Experience through E-Learning Platforms to Enhance Creative Potential and Language Performance - Hafizoah, Kassim (Vietnam National University - Ho Chi Minh City Press, 2019)
Creativity is a rare topic in language learning conversations, often overshadowed by the emphasis on student performance or achievement in language competencies. With technology, discussions mostly linger around the application of appropriate teaching approaches and/or learning strategies. Yet, with its prowess, technology provides huge opportunities for teachers to engineer learning experiences that could bring about student creativeness. Such learning experiences, if appropriately and cognitively strategize could motivate students to enhance not only their creative abilities but also language performance. In this presentation, I will share the development of a learning model called Creative Strategy Learning Model (CSLM) which integrates creative and strategic thinking taxonomies to assist learners to use their creative cognitive abilities to cognitively strategize their learning. In addition to the in-class learning experience, e-learning platforms such as Moodle and Edmodo were used as a platform to create a learning experience where students can communicate their ideas and follow their progress in the speaking and writing classes. The application of this model in the speaking and writing classes illustrates its importance in assisting students to enhance their public speaking performance, and essay writing skills. Student feedback revealed that the opportunity to see the performance in their creative ability is a boost to better improve their speaking and writing abilities.